Static and fatigue behaviors of corroded stud connectors in weathering steel–concrete composite beams. (1st December 2022) - Liu, Tai; Nie, Xin; Zeng, Jiahua; Su, Han
Highlights: The weathering steel beam improves the corrosion fatigue behavior of welded studs. γ-P-S-N curves of studs are derived and compared with existing codes. An analytical model is developed to predict the fatigue life of corroded studs. Evolution of plastic slip and elastic stiffness throughout the life cycle is revealed. Abstract: In steel–concrete composite structures, stud connectors are applied to achieve the composite action between steel beam and concrete slab. For sea-crossing suspension bridges and cable-stayed bridges, hogging moment regions spread over the full span, which induces tensile stress and unexpected cracking in concrete slabs. Stud connectors embedded in cracked concrete slabs are confronted with higher damage risk induced by atmospheric corrosion. This study investigated the static and fatigue behaviors of corroded stud connectors in weathering steel–concrete composite beams through accelerated corrosion and push-out tests. The ultimate shear strength and load-slip relationship of studs are correlated with corrosion defects on studs. Test results from 15 fatigue push-out specimens indicate a fatigue life reduction up to 80% for corroded studs, basically attributed to accelerated crack initiation from corrosion pits. S-N curves with confidence levels are derived and applied for safety assessment on existing codes. An analytical model reflecting the effect of corrosion is proposed for fatigue life prediction. Evolution of plastic slip and elastic stiffness throughout the fatigue life of studs is further evaluated and the empirical model of residual static performance with a given load history is formulated.